Vector control of asymmetrical six-phase synchronous motor. Issue 1 (31st December 2016) - Iqbal, Arif; Singh, G.K.; Pant, Vinay
Abstract: Vector control scheme has been well adopted for higher performance applications of AC motor. Therefore, this paper presents an extensive development and investigation of vector control scheme for asymmetrical six-phase synchronous motor in a new two-axis (M–T) coordinate system. Phasor diagram has also been developed in a simplified way, followed by its implementation technique. Analytical results have been presented for four-quadrant operation of synchronous motor, employing the developed vector control scheme. In analytical control model, common mutual leakage reactance between the two winding sets occupying same stator slot has been considered.